Analisis Capital Asset Pricing Model (Capm) Dalam Menentukan Keputusan Investasi Saham - Rahma Rusdi, Nur; Tawe, Amiruddin; Nurman, Nurman; Anwar, Anwar (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
This study aims to analyze investment decisions on LQ45 index stocks for the period 2017-2021 using the Capital Asset Pricing Model (CAPM) method. This type of quantitative research is descriptive. The population in this study are companies listed on the Indonesia Stock Exchange. The sample is all company shares listed in the LQ45 index for the period February 2017-December 2021, namely 67 company shares. Data collection techniques used are literature and documentation. The data analysis technique used is the Capital Asset Pricing Model (CAPM). The results showed that the systematic risk and the expected rate of return have a linear relationship and there are 26 company shares which are included in efficient shares and 41 company shares which include inefficient shares.